Database systems a practical approach to design, implementation, and management - Connolly, Thomas M.; Beg, Carolyn E. (Pearson Education Limited, 2015)
This book is ideal for a one- or two-term course in database management or database design in an undergraduate or graduate level course. With its comprehensive coverage, this book can also be used as a reference for IT professionals. This text introduces the theory behind databases in a concise yet comprehensive manner, providing database design methodology that can be used by both technical and non-technical readers. The methodology for relational Database Management Systems is presented in simple, step-by-step instructions in conjunction with a realistic worked example using three explicit phases-conceptual, logical, and physical database design. Teaching and Learning Experience This program presents a better teaching and learning experience-for you and your students. It provides: Database Design Methodology that can be Used by Both Technical and Non-technical Readers ; A Comprehensive Introduction to the Theory behind Databases ; A Clear Presentation that Supports Learning.